2017
DOI: 10.18632/oncotarget.18076
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of an X-linked primate-specific epididymal microRNA cluster in unexplained asthenozoospermia

Abstract: Asthenoszoopermia, characterized by reduced sperm motility, is one of the primary forms of male infertility. Whereas most cases were diagnosed into unexplained asthenozoospermia (UA) because the etiology cannot be identified. In animal models, epigenetic dysregulation in epididymis can impair sperm maturation and result in asthenozoospermia. However, researches of epididymal epigenetic regulation on humans are impeded by the difficulty in obtaining epididymal tissues. We previously identified cell-free seminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 36 publications
0
28
1
Order By: Relevance
“…Given that germ cells are in direct contact with SCs [64], this supports a model in which miR-743b-3p and miR-878 regulate gene expression in SCs to influence germ cell differentiation. In support of the possibility that the Fx-mir cluster is important for spermatogenesis, a recent study reported that several human FX-MIR family members-including miR-891b, miR-892b, miR-892a, miR-888, and miR-890-are dysregulated in men with asthenozoospermia [65].…”
mentioning
confidence: 99%
“…Given that germ cells are in direct contact with SCs [64], this supports a model in which miR-743b-3p and miR-878 regulate gene expression in SCs to influence germ cell differentiation. In support of the possibility that the Fx-mir cluster is important for spermatogenesis, a recent study reported that several human FX-MIR family members-including miR-891b, miR-892b, miR-892a, miR-888, and miR-890-are dysregulated in men with asthenozoospermia [65].…”
mentioning
confidence: 99%
“…In trying to unravel the molecular mechanisms of idiopathic AZS, recent studies have demonstrated dysregulation of miRNAs in total semen (Liu, Cheng, Gao, Wang, & Liu, ; Tian et al, ) seminal plasma (Qing et al, ; Wang et al, ; Zhou, Wang, et al, ; Zhou et al, ) and spermatozoa (Abu‐Halima et al, ; Salas‐Huetos et al, ; Zhou, Zhou, et al, ; Zhou et al, ) of AZS men. Dysregulation of miRNAs may arise from numerous mechanisms containing polymorphisms and/or mutation in these noncoding RNA (Lu et al, ), and also, these dysregulated miRNAs may enact through various mechanisms in molecular pathology of AZS.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of miRNAs is probable to play an important role in male infertility (Khazaie & Nasr Esfahani, ). Previous studies demonstrated altered miRNAs in total semen (Tian et al, ), seminal plasma (Qing et al, ; Wang et al, ; Zhou, Wang, et al, ) and spermatozoa (Abu‐Halima et al, ; Salas‐Huetos et al, ; Zhou et al, ; Zhou et al, ) of AZS men. In line with these studies, it was intended to evaluate the miRNA expression profile in spermatozoa of unexplained AZS men.…”
Section: Introductionmentioning
confidence: 94%